Radical-scavenging activity and antibacterial activity of Yahong-yahong (Hydrocotyle vulgaris) crude ethanolic leaf extract. - Ygrubay, Hans Joshua U.; Ricarte, Marjhun A. (Hans Joshua U. Ygrubay, 2018)
The radical scavenging and antibacterial activities of Hydrocotyle vulgaris crude ethanolic leaf extract were evaluated in this study. The phytochemical constituents of the ethanolic extract was also estimated. The radical scavenging activity was determined using the DPPH-radical scavenging assay with quercetin (SC50=4.75 +/- 0.19 ppm) and gallic acid (SC50= 6.67 +/- 0.12 ppm) used as standards. The antibacterial activity against Staphylococcus aureus and Escherichia coli was determined using the disk diffusion assay with Streptomycin (10 mg/mL) used as positive control. Finally, the phytochemical composition was estimated using thin layer chromatography. The H. vulgaris crude ethanolic leaf extract was found to have antioxidant (SC50=911.90 +/- 33.46 ppm) and antibacterial activities although less than those of the standards. The solvent systems 5:4:1 toluene-acetone-formic acid (TAC) and 2:8.5:3 benzene-chloroform-methanol (BCM) produced the best results with seven and five spots, respectively. The ethanolic extract was found to contain phenolic compounds which would account for its antioxidant and antibacterial properties.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.